The Origins of the Cold War in Southeast Asia: The Case of Communist Party of Malaya (1948-1960) - A Special Branch Perspective - Leon Comber (Kajian Malaysia, 2009)
The origins of the Malayan Emergency (1948–1960) have been debated over the years in both the academic world and in the intelligence community. This paper incorporates the contemporaneous views of the Malayan Special Branch that have not been recorded previously. It also examines the role of Lawrence (Lance) Sharkey, the acting SecretaryGeneral of the Australian Communist Party, who was in Singapore en route back to Australia after attending the February 1948 Conferences in Singapore, in allegedly passing instructions to the Communist Party of Malaya (CPM) to revolt against the British colonial government in Malaya. The essay will conclude that there is little evidence of any direct Soviet intervention in the decision made by the CPM to revolt, and it will argue that the decision to resort to armed conflict was made after its failure to establish a Communist People’s Democratic Republic by “open front” activities.